2022
DOI: 10.1177/00469580221082356
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of South African Hypertension: Comparative Analysis of the Classical and Bayesian Quantile Regression Approaches

Abstract: Hypertension has become a major public health challenge and a crucial area of research due to its high prevalence across the world including the sub-Saharan Africa. No previous study in South Africa has investigated the impact of blood pressure risk factors on different specific conditional quantile functions of systolic and diastolic blood pressure using Bayesian quantile regression. Therefore, this study presents a comparative analysis of the classical and Bayesian inference techniques to quantile regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…21 However, with the increased interest in machine learning methods in medical research, quantile regression has recently attracted attention as a valuable data analysis tool in the medical research area. 13 Kuhudzai et al 22 is the first study which indicated the impact of blood pressure risk factors in South Africa using BQR model. The study showed that the BQR model performs more accurate modeling for the hypertension estimate than classical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, with the increased interest in machine learning methods in medical research, quantile regression has recently attracted attention as a valuable data analysis tool in the medical research area. 13 Kuhudzai et al 22 is the first study which indicated the impact of blood pressure risk factors in South Africa using BQR model. The study showed that the BQR model performs more accurate modeling for the hypertension estimate than classical approaches.…”
Section: Discussionmentioning
confidence: 99%